2019
DOI: 10.2147/opth.s229335
|View full text |Cite
|
Sign up to set email alerts
|

<p>Analysis of Bimatoprost-Induced changes on Rabbits eyelash Follicle: Clinical and Electron microscopic study</p>

Abstract: ObjectiveTo analyze ultrastructural changes of rabbits' eyelash follicles treated with bimatoprost eye drops to increase our knowledge of how this drug works.MethodsThe study included 15 clinically healthy male rabbits. All rabbits were treated with bimatoprost 0.03% daily for 4 weeks with one drop of the topical eye drops applied to the conjunctival fornix of the right eyes; left eyes were used as controls. Eyelash lengths were measured before and after treatment. The eyelid of each animal was dissected for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…explored the changes in the eyelashes of 15 rabbits after treatment with topical bimatoprost 0.03% daily to the right conjunctival fornix for 4 weeks, using the left eye as the control. The authors found that in addition to increased length, thickness, and pigmentation, there was an increased number of eyelashes within the same hair follicle and increased tensile strength of the hair 17 . To our knowledge, these particular findings have not yet been described in humans.…”
Section: Prostaglandin Analogsmentioning
confidence: 83%
See 1 more Smart Citation
“…explored the changes in the eyelashes of 15 rabbits after treatment with topical bimatoprost 0.03% daily to the right conjunctival fornix for 4 weeks, using the left eye as the control. The authors found that in addition to increased length, thickness, and pigmentation, there was an increased number of eyelashes within the same hair follicle and increased tensile strength of the hair 17 . To our knowledge, these particular findings have not yet been described in humans.…”
Section: Prostaglandin Analogsmentioning
confidence: 83%
“…The authors found that in addition to increased length, thickness, and pigmentation, there was an increased number of eyelashes within the same hair follicle and increased tensile strength of the hair. 17 To our knowledge, these particular findings have not yet been described in humans.…”
Section: Bimatoprostmentioning
confidence: 84%